Lokajībane Śrīrāmakrshṇa - Someśvarānanda, Swami (Sujana Pābalikeśanas, 1983)
Folkloristic and sociological study of the philosophy of Ramakrishna, 1836-1886, Hindu religious leader; includes a note on the Ramakrishna movement.